P5_4 Bunker Busters: A Gift from Space - Shaikh, Hasan; Agrawal, Rusi; Ruprai, Amrik; Singh, Jagraj (Physics Special Topics, 2021)
The effectiveness of a 10 m Tungsten rod, dropped from LEO, is evaluated as a practical bunker buster and was found to impact at the surface at Mach 23, producing a non-explosive yield ≈417 times that of the GBU-57 Massive Ordnance Penetrator (MOP), while having a similar penetration through soil and a maximum depth of 22 m through solid steel.